Proceedings of the 21st Koli Calling International Conference on Computing Education Research 2021
DOI: 10.1145/3488042.3488049
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Skills and Demographic Factors in CS1

Abstract: Motivation Prior studies have established that training spatial skills may improve outcomes in computing courses. Very few of these studies have, however, explored the impact of spatial skills training on women or examined its relationship with other factors commonly explored in the context of academic performance, such as socioeconomic background and self-efficacy.Objectives In this study, we report on a spatial skills intervention deployed in a computer programming course (CS1) in the first year of a post-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Another recent inquiry determined the effectiveness of an online spatial-skills training program via the Revised PSVT:R [33]. In the context of freshmen studying computer programming, the online program was noted to be effective at boosting spatial abilities, primarily for students identified as having a spatial-skills deficiency by a preliminary screening for spatial ability [55].…”
Section: Ages 18 Years To 22 Years-university and Graduate Students (A5)mentioning
confidence: 99%
“…Another recent inquiry determined the effectiveness of an online spatial-skills training program via the Revised PSVT:R [33]. In the context of freshmen studying computer programming, the online program was noted to be effective at boosting spatial abilities, primarily for students identified as having a spatial-skills deficiency by a preliminary screening for spatial ability [55].…”
Section: Ages 18 Years To 22 Years-university and Graduate Students (A5)mentioning
confidence: 99%
“…Parkinson & Cutts discovered that there was a correlation between spatial skills and exam scores in a CS0 cohort [29] and separately with a test of expression evaluation [31]. Ly et al also observed correlations between spatial skills and final module grades in a CS1 cohort [19]. The correlation between spatial skills and various forms of CS assessment and success has, therefore, been explored in many areas.…”
Section: Spatial Skills Are Related To Computing Science Successmentioning
confidence: 99%
“…These results indicate that there is an increase in spatial skills across semester 1 and the full year which is unlikely to be a false positive, but the minimal gains across semester 2 are much more likely to be due to a false positive based on the high p-value. [19]. To determine whether this applied in computing instruction, gains were calculated for the first semester for all students with enough data by subtracting their PSVT:R 1 score from their PSVT:R 2 score.…”
Section: Changes Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, students were given a pre-and post-test in spatial skills. Of 668 students enrolled in the CS1 module, for this study can be found in work by Ly et al [6].…”
Section: Case 5: Entire Cohort Online Sst Platformmentioning
confidence: 99%